2013
DOI: 10.1177/1933719112472733
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Rat Vaginal Smooth Muscle Contractility and Morphology

Abstract: The objective of this study was to define the regional differences in rat vaginal smooth muscle contractility and morphology. We evaluated circumferential segments from the proximal, middle, and distal rat vagina (n ¼ 21) in vitro. Contractile responses to carbachol, phenylephrine, potassium chloride, and electrical field stimulation (EFS) were measured. Immunohistochemical analyses were also performed. The dose-response curves for carbachol-and phenylephrine-dependent contractions were different in the distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 12 publications
6
20
0
Order By: Relevance
“…Our results in sheep are in line with a study in rats which showed significant regional differences of vaginal wall contractility [9]. We restricted our testing to the posterior vaginal wall tissue due to the different anatomical location of the urethral orifice between sheep and humans.…”
Section: Discussionsupporting
confidence: 88%
“…Our results in sheep are in line with a study in rats which showed significant regional differences of vaginal wall contractility [9]. We restricted our testing to the posterior vaginal wall tissue due to the different anatomical location of the urethral orifice between sheep and humans.…”
Section: Discussionsupporting
confidence: 88%
“…This observation may contribute to the hypersensitivity described above. The M2 and M3 receptors have been previously demonstrated in vaginal tissue and muscarinic activation induces contraction, although their physiologic role remains unknown 14,23 . The upregulation of M2 we demonstrate at 3 days, might therefore further explain the earlier described hypersensitivity.…”
Section: Discussionsupporting
confidence: 57%
“…To document the functional effect of PNC + VD on the smooth muscle layer of the vaginal wall, strips of vaginal tissue were tested in organ baths, as described previously by Skoczylas et al 14 After euthanasia, the vagina excised in toto and placed in ice cold Krebs solution (in mM: 118 NaCl, 4.7 KCl, 3.3 MgSO 4 , 5.5 glucose, 2 Na pyruvate, 1.5 KH 2 PO 4 , 25 NaHCO 3 , 3.3 CaCl 2 ). A circumferential strip from the middle vagina measuring 3 × 7 mm was suspended with custom‐made tissue clamps, which were attached to a stationary hook on one side and the force transducer (Harvard Apparatus, Holliston, MA) on the other side.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations